Reflecting on practice for STEM educators : a guide for museums, out-of-school, and other informal settings - Tran, Lynn Uyen; Halversen, Catherine (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Reflecting on Practice for STEM Educators is a guidebook to lead a professional learning program for educators working in STEM learning environments. Making research on the science of human learning accessible to educational professionals around the world, this book shows educators how to relate this research to their own practice. Educators' collective work broadens the scope of an organization's reach, and through this effort, the organization grows its social capital in its local community and beyond. This book offers opportunities to engage in processes that lead toward organizational learning by attending to the professional growth of the educators. Tran and Halversen show how learning together can shape the language and meanings by which educators do and talk about their work to support visitors' experiences. The book provides guidance on how teams of educators can build community as they engage in reflective practice. Reflecting on Practice for STEM Educators will be essential reading for leaders of any organization that aims to educate and engage the public in science, technology, engineering, and mathematics. It will be particularly useful to educators who work in museums, zoos, aquariums, botanical gardens, youth organizations, after-school programs and nature, science and conservation centers"--
Learning, reflections, and science : introduces the routines and foundations of the Reflecting on Practice program -- How people learn : articulates how learning builds on prior knowledge -- Learning conversations : emphasizes that talking is learning -- Objects and design : spotlights how we use objects in our learning designs.
OCLC-licensed vendor bibliographic record.
Keywords: Science -- Study and teaching -- United States; Technology -- Study and teaching -- United States; Engineering -- Study and teaching -- United States; Mathematics -- Study and teaching -- United States; Reflective teaching -- United States; Non-formal education -- United States; EDUCATION / Professional Development; EDUCATION / Non-Formal Education